Avaliação fungitóxica do óleo essencial de de Tanaecium nocturnum (bar.Rodr.) Bur.e Shum sobre o Aspergillus flavus isolado da castanha-do-Brasil (Bertholetia excelsa) - Pimentel, Flávio Araújo (2010)
The present work sought to evaluate the fungitoxic activity of the essential oil from fresh Tanaecium nocturnum fresh leaves on Aspergillus flavus isolated from Brazil nuts, using contact and fumigation techniques. The results of bioassays performed up to 10 days of incubation demonstrated that total inhibition of mycelial growth occurred when using the essential oil at concentrations of 782 ppm (contact technique) and 1000 ppm (fumigation technique). In both techniques, the essential oil inhibited the formation of spores at the concentration of 500 ppm. No significant difference in the results presented by the two techniques was observed in the first five days of incubation. After this period, the essential oil showed a reduction in activity at concentrations lower than 1000 ppm in the fumigation test. The fungitoxic activity of the essential oil on the organism studied can be attributed to the presence of benzaldehyde (major component of the essential oil), in combination with other compounds also present in this oil, such as, benzyl alcohol, benzyl benzoate and mandelonitrila.